Data Baru dari Marga Selaginella - Yuni Krisnawati; Yunita Wardianti; Yuli Febrianti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the types of Selaginella that exist in Curug Embun Waterfall, North Lubuklinggau I, South Sumatra. This research method is a qualitative descriptive type. Sampling using roaming and documentation methods. Data were analyzed by observing specimens and identification by scanning morphological characters. The results showed that the kinds of Selaginella found were Selaginella wallichii (Hook. & Grev.) Spring, Selaginella intermedia (Blume) Spring., Selaginella plana (Desv.) Hieron., Selaginella doederleinii Hieron, Selaginella willdenowii (Desv.) Backer., Selaginella ornata Spring., Selaginella sp.1 and Selaginella sp.2. In conclusion, there are eight types of Selaginella in the Curug Embun Waterfall area. Keywords: Curug Embun Waterfall, Lubuklinggau, Selaginella